The Effectiveness of Corruption Law Enforcement in Indonesia and Malaysia: A Comparative Analysis of Criminalization, Asset Recovery, and the Al-'Uqubah Principle - Wardatul Jannah; Ramadani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This article analyzes the effectiveness of law enforcement to eradicate corruption in Indonesia and Malaysia by focusing on the formulation of penalties, asset recovery, and the relevance of the principle of al-'uqubah in Islamic criminal law. The main problem of this study is the distance between the severe criminal threat and the effectiveness of the punishment in producing a deterrent effect and the return of state losses. The research uses normative legal methods with a statutory approach, a conceptual approach, and a comparative approach. Primary legal materials include the Indonesian Corruption Eradication Law, the Malaysian Anti-Corruption Commission Act 2009, the United Nations Convention against Corruption, and regulations related to asset recovery. Secondary legal materials were obtained from journals, books, KPK reports, MACC/MACC, Indonesia Corruption Watch, and Transparency International. The analysis was carried out qualitatively prescriptively with indicators of proportionality of punishment, effectiveness of asset recovery, consistency of enforcement, and conformity with the principles of maslahah mursalah and radd al-mazalim. The results of the study show that Indonesia has a severe criminal threat, but still faces the problem of inconsistency of sentences, the lack of optimal use of substitute money crimes, and the weak use of money laundering instruments to pursue the results of corruption. Malaysia has a more proportionate normative design through fines of at least five times the gratuity value and stronger asset tracing mechanisms, but its effectiveness still has to be read with caution as the available asset recovery data is not always on par with Indonesia's. This article recommends the reformulation of proportional fines, strengthening non-conviction-based asset forfeiture, integrating enforcement data, and strengthening the principle of al-'uqubah as an ethical framework for corruption punishment oriented towards prevention, recovery, and public benefit.